(untitled) (Journal SCIENCEVOLUTION, 2026)
Carbon quantum dots (CQDs) are fluorescent nanomaterials widely studied due to their low toxicity and remarkable optical properties, which enable their use in various applications. Agro-industrial residues, such as Coffea arabica waste, represent a sustainable carbon source for nanomaterial synthesis within circular economy strategies. The objective of this study was to evaluate the effect of two green synthesis routes, pyrolysis and microwave-assisted synthesis, on the structural and optical properties of CQDs obtained from spent coffee grounds. The precursor was pretreated for 24 hours and subsequently subjected to thermal pyrolysis at 400°C under controlled conditions, whereas the microwave-assisted method employed irradiation at 750 W and 200°C. The obtained samples were purified and characterized using photoluminescence spectroscopy and X-ray diffraction. CQDs synthesized via pyrolysis exhibited a blue emissions (440–460 nm) with particle diameters between 10 and 12 nm, whereas the microwave method produced emissions around 345 nm with particle diameters 8 nm. The results indicated that pyrolysis produces higher fluorescence intensity, highlighting its potential for optoelectronic applications.